Perlindungan Hukum Terhadap Konsumen Dalam Pengiriman Barang Melalui Jasa PT.Global Jet Express - Rahmad Ready Kurniawan; Faisol Faisol; Renaldy Afriyanto; Ainur Gufron; Ahmad Syauqi Bawashir (An-Nisa: Journal of Islamic Family Law, 2024)
As time goes by, science and technology also develop, especially in the industrial sector. The increasing popularity of online shops means that online transactions are also increasing, which in this case involves expedition companies in sending goods between cities or regions. One of them is PT. Global Jet Express (J&T Express). The process of sending goods through J&T Express greatly helps human activities, but there are obstacles experienced by expedition companies such as late delivery of goods, damage, and even loss. These problems will certainly harm consumers. The research method includes a type of research that is normative juridical. The results of the study show that consumers have the right to receive compensation, damages and/or replacement, if the goods and/or services received do not comply with the agreement or are not as they should be. Legal efforts to prevent consumers from being harmed due to goods used in a damaged condition through the fulfillment of the obligations of business actors to carry out business activities in good faith